Discussion of The Visibility of the Auditor's Disclosure of Deviance from APB Opinion: An Empirical Test - Buckley, John W. (Journal of Accounting Research, 1969)
The Council of the AICPA issued a Special Bulletin' in October, 1964, which provides that departures from APB Opinions, where they are supported by substantial authoritative support, be disclosed (1) in the auditor's opinion, or (2) in a footnote to the financial statements-at the auditor's option. The subject paper is concerned with (1) the equivalence of these two methods of disclosure in terms of their visibility and impact on various classes of users, and (2) on the significance of disclosing a departure from the viewpoint of its being a warning or signal to the reader to pay closer attention to the statements than he would otherwise. The hypotheses of the researchers and their findings are summarized in Table 1. While some of the findings may have been expected, based on the assumptions underlying the experiment, two were a distinct surprise: 1. That there is no difference in the apparent visibility of footnotes vis-a-vis the auditor's report; and 2. That a warning (contained in the auditor's report) placed at the end of the financial statements was more potent than a warning at the beginning. These and other specifics of the experiment itself will be discussed following comments on some general implications of the project.